(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
The work is guided by a deductive methodology, with initially basic and descriptive designs, added to a qualitative approach and adoption of bibliographic procedures. We sought to understand the work of Roberto Gargarella. Latin American Constitutionalism (1810-2010). The Engine Room of the Constitution. Next, the Brazilian reality was analyzed, especially after the 1988 Constitution, highlighting the aspect of the formation of a coalition presidentialism that stands out after the promulgation of this Major Law, a moment in which a period of redemocratization also strengthened. It is from this spectrum that the basis for what the political reality of Brazil is today is, marked by a strong coalition presidentialism, where citizens are removed from the country’s most important decisions. One of the most tangible examples of this perception is not precisely called “Secret Budget”, which will also be the object of analysis based on the author’s work. Finally, the work seeks to reflect on how Roberto Gargarella’s structure of thought is reflected in the Brazilian reality, seeking to answer whether society has reached the Engine Room, as proposed by the author in a democratic Constitutionalism.